Moderasi Beragama: Menghidupkan Ruang Pertemuan Antar Umat Beragama bagi Gen-Z di Wilayah Cinunuk Kecamatan Cileunyi - Andreas Doweng Bolo; Oscar Yasunari; Topik Mulyana; Sophan Ajie (Jurnal Pengabdian Masyarakat Waradin, 2025)
Religious moderation has become a serious concern for the government as it strives to maintain interfaith harmony in Indonesia. In 2019, the Ministry of Religious Affairs of the Republic of Indonesia published a book entitled Moderasi Beragama (Religious Moderation). In this publication, it is explained that the term “moderation” is derived from the Latin word denoting “balance” or “moderation” and from the Arabic term wasath or wasathiyah, which signifies centrality, fairness, and equilibrium. To achieve this ideal, it is necessary to design and expand interfaith meeting spaces – especially those aimed at young people (Generation Z) from diverse religious and belief backgrounds. The Cinunuk area is part of the pastoral care of the Santa Odilia-Cicadas Parish in Bandung and is home to approximately 350 Catholic households living in close proximity to their Muslim neighbors. On several occasions, the Catholic community in Cinunuk has organized joint community initiatives, such as free medical services and the distribution of essential food supplies. Furthermore, the Catholic community has previously engaged in interfaith activities with the Gusdurian group and has maintained positive relations with both the Attamur and Azzakiyyah Islamic boarding schools in the Cileunyi sub-district. To further strengthen intercommunal interactions and foster a dynamic dialogue between the Catholic community in Cinunuk and their Muslim counterparts in the region, a collaborative activity has been designed to reinforce the moderate stance that has been consistently practiced.